Agrimol B inhibits colon carcinoma progression by blocking mitochondrial function through the PGC-1α/NRF1/TFAM signaling pathway - Xiang, Dongyang; Yang, Wenjuan; Fang, Zihan; Mao, Jialei; Yan, Qiuying; Li, Liu; Tan, Jiani; Yu, Chengtao; Qian, Jun; Tang, Dongxin; Pan, Xiaoting; Cheng, Haibo; et al. (Frontiers in Oncology, 2022)
Abstract Background: The activation of peroxisome proliferator-activated receptor-γ coactivator 1α (PGC-1α) stimulates the transcription of the downstream target proteins, mitochondrial transcription factor A (TFAM) and nuclear respiratory factor 1 (NRF1), which induces mitochondrial biogenesis and promotes colorectal tumorigenesis. Agrimol B (Agr) is a constituent of Agrimonia pilosa Ledeb. that exerts anticancer effects. Herein, we aimed to investigate the antitumor activity of Agr and its mechanism of action. Methods: The interaction between Agr and PGC-1α was predicted by molecular docking. After the treatment with different concentrations of Agr (0, 144, 288, and 576 nM), the cell viability, migration rate, proliferation rate, and apoptosis rate of human colon cancer HCT116 cells were determined. Mitochondrial activity, cellular reactive oxygen species (ROS), and mitochondrial membrane potential were assessed to measure the regulatory effect of Agr on mitochondrial function. Western blot assay (WB) was used to examine the expression of PGC-1α, NRF1, and TFAM, as well as of the pro-apoptotic proteins, Bax and Caspase-3, and of the antiapoptotic protein (Bcl-2). Finally, subcutaneous tumor xenograft model mice were used to evaluate the effect of Agr on colorectal cancer (CRC) in vivo. Results: The molecular docking results revealed a high likelihood of Agr interacting with PGC-1α. Agr inhibited the proliferation and migration of HCT116 cells, promoted ROS production and mitochondrial oxidative stress, and inhibited mitochondrial activity, and decreased mitochondrial membrane potential. Agr induced cell apoptosis and in combination with PGC-1α, impaired mitochondrial biogenesis and suppressed the expression of NRF1 and TFAM. Agr also suppressed the expression of Bcl-2 and Cleaved-Caspase-3 and increased the expression of Bax and Caspase-3. In addition, the in vivo antitumor effect and mechanism of Agr was confirmed by using a subcutaneous tumor xenograft mouse model. Conclusions: Our findings demonstrated that Agr regulates the expression of PGC-1α, thereby inducing mitochondrial dysfunction and promoting tumor cell apoptosis. This work highlights the potential of Agr as a promising therapeutic candidate in CRC.